Rancang Bangun Trainer PLTS On Grid dan Off Grid Sebagai Penunjang Praktikum - Sahar, Muzni; Hayati, Mardhatillah; Syahrizal, Syahrizal; Gunawan, Arif; Alfizah, Alfizah (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Solar Power Plant is a system that can produce electrical energy by converting solar thermal energy absorbed by solar cells. In this study, a PLTS practicum module design was created which contained two systems, namely On Grid and Off Grid. Where the purpose of this research is to make it easy for students to understand the differences between the two systems and the operation of the PLTS. In the On Grid system, the output of the inverter can be connected directly to the public electricity grid, in this case PLN by using a Grid Tie inverter which has synchronization in it. And also in this on grid system does not use a battery to store its power reserves. Meanwhile, it is different from an off-grid system, which uses a battery and cannot be connected directly to the public electricity network. In the Off Grid system the resulting voltage is 223.60 Volts and in the On Grid System is 236.83 Volts. Testing is carried out with 2 different loads on each system. It can be concluded that the PLTS system designed Off Grid and On Grid can run well. Keywords: PLTS, On Grid. Off Grid, Practicum Trainer